Water-soluble phthalocyanines with non-peripheral naphthoxy-sulfonate substituents: computational docking, biological and sono-photochemical investigations - Gunsel, Armagan; Karanlik, Ceren Can; Taslimi, Parham; Gunsel, Hilal; Taskin-Tok, Tugba; Bilgicli, Ahmet T.; Ozden, Eda Mehtap; Gulcin, Ilhami; Erdogmus, Ali; Yarasir, M. Nilufer (SPRINGERNATURE, 2026)
This study reports the synthesis of a novel ligand, sodium 6-(2,3-dicyanophenoxy)naphthalene-2-sulfonate (1), and the corresponding non-peripherally substituted metallophthalocyanines (MPcs) [M = Zn(II) (2), Ga(III) (3); X = Cl, In(III) (4); X = Cl]. These compounds were functionalized with 6-naphthoxy-2-sulfonic acid sodium salt groups. Given the limitations of conventional photodynamic therapy (PDT), we investigated the potential of sonophotodynamic therapy (SPDT), a dual-modality approach combining light and ultrasound, to enhance singlet oxygen ((1)O2) production. Among the synthesized metallophthalocyanines, the zinc(II) complex (2) shows the highest (1)O2 production in both organic and aqueous media under both photochemical and sonophotochemical conditions, showing promise for SPDT applications. Furthermore, the inhibitory effects of these complexes on acetylcholinesterase (AChE) and human carbonic anhydrase isoenzymes (hCA I and II), important targets for Alzheimer's disease, glaucoma, and epilepsy, were evaluated. The compounds showed strong inhibition with Ki values ranging from 130.31 +/- 6.18 to 157.47 +/- 9.37 mu M for hCA I (compared to AZA: 177.41 +/- 11.40 mu M), 99.18 +/- 8.13 to 106.72 +/- 8.50 mu M for hCA II (compared to AZA: 143.51 +/- 9.94 mu M) and 0.31 +/- 0.03 to 1.21 +/- 0.01 mu M for AChE (compared to TAC: 1.24 +/- 0.21 mu M). Molecular docking revealed strong binding affinities: In(III)-Pc (4) showed the highest affinity for AChE (BE: -26.96 kcal/mol), while Ga(III)-Pc (3) preferentially bound to hCA I and II (BE: -13.90 and - 15.39 kcal/mol, respectively). These findings position the synthesized MPcs as multifunctional agents for SPDT and enzyme-targeted therapies.
Keywords: Phthalocyanine; Synthesis; Singlet oxygen; Bioactivity; In silico study; PHOTODYNAMIC THERAPY; ZINC PHTHALOCYANINES; METAL-FREE; PHOTOSENSITIZERS; GALLIUM; AGGREGATION; Biochemistry & Molecular Biology; Biophysics; Chemistry